Inhibitory effects of allelopathic crops on seedling growth of weed Hypericum triquetrifolium Turra - ÖZYİĞİT, İBRAHİM İLKER (ALLELOPATHY JOURNAL, 2019)
In Laboratory bioassays and Pot culture, we determined the effects of aqueous extracts of 7-allelopathic crops [Alfalfa (Medicago sativa L.), Sorghum (Sorghum bicolor L.), Sunflower (Helianthus annuus L.), Rape (Brassica napus L.), Rye (Secale cereal L.), Barley (Hordeum vulgare L) and Oat (Avena saliva L)] on the seedling growth of weed Hypericum triquetrifolium. In first Lab. bioassay, barley and rape were found most phytotoxic to Hypericum seedlings growth. Then these two crops effects were further tested in pot experiments, with different residues rates (R1, R2, R3 for rape and B1, B2, B3 for barley) and at 3-stages of Hypericum development (S1: Hypericum pre-germinated seeds, S2: 4-Hypericum leaves developed and S3: formation of branches). Barley and rape residues proved very phytotoxic to root length of Hypericum (-74.51% and -72.29% respectively). The effects of both crops residues on H. triquetrifolium and root growth were dose dependent and the highest rape residue rate (8 g/pot) caused -67 % inhibition than control. The crop residues were more phytotoxic to Hypericum in early stages of development. The GC-MS analysis of rape residues identified 10-allelopathic compounds.
Keywords: Alfalfa; allelopathy; aqueous extract; Avena sativa; barley; Brassica napus; Helianthus annuus; Hordeum vulgare; Hypericum triquetrifolium; Medicago sativa; oat; rape; residue; root growth; rye; Secale cereale; sorghum; Sorghum bicolor; sunflower; WILD OAT; L.; GERMINATION; SORGHUM; EXTRACT; SATIVA; BARLEY; WHEAT; RICE; GLUCOSINOLATE